Comparative Study of the Sorogan Method and Deliberation Method to Improve Kitab Kuning Reading Ability - Miftahuddin; Nuruddin, Muhammad (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
This study was to determine how the comparison between the sorogan method and the method of deliberation on the ability to read the book on the students of Madrasah Ihya